Using Cards to Improve the Alphabetical Recognition Ability of Early Childhood - Mujiati, Ririn; Hendrik, Siswono; Sugiarto, Muhammad Agus (STAI Auliaurrasyidin Tembilahan, 2025)
Children’s reading ability is now the main basis for taking the next level of education. The level of reading ability becomes a priority scale for early childhood education, and it needs to be developed comprehensively. One effort to encourage these capabilities is to use representative media, such as letter cards. This research aims to improve the student’s ability to recognize letters using letter cards. This is classroom action research. The research has taken place in group A aged 4-5 years Kartini II Kindergarten PGRI Rambipiju. There were 16 students involved in this research. This used tests and observation sheets with 1-to-4-star assessment criteria such as students being able to show letters, and students being able to order letters. The students should therefore get a minimum of three stars in aspects observed for individual completeness; and 75% of the total number of students for classical completeness. The data were then analyzed both qualitatively and quantitatively. The results show that 56% of the total number of students or 9 students completed cycle I and 87% or 14 students completed cycle II. Accordingly, the letter cards can improve the student’s ability to recognize the alphabet.